Kewenangan BPN dalam Mencabut Sertipikat Hak Milik Atas Tanah Karena Cacat Administrasi Berdasarkan Asas Contrarius Actus - Imran; Moh Rizaldi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
Cases of administratively flawed land certificates are increasing, both caused by negligence and on purpose. Interestingly, instead of trying to resolve it, the Government has issued PP No. 18 of 2021 in which one of the provisions requires an administrative disability certificate that has been issued for more than five years, to be tried by a court. The problems raised are first, how is the legal politics of the contrarius actus principle; Second, how should BPN officials respond to the certificate? Through a statutory and conceptual approach, this study concludes that firstly the principle of contrarius actus is empowered to resolve administrative cases without amputating the court's authority to adjudicate; second, BPN officials have the authority to cancel administrative certificates that are more than five years after issuance.